'What have the Romans ever done for us?' Postcolonialism, mimicry and hidden transcripts in the book of Revelation. (October 2014) - Low, U-Wen
This article examines and discusses Stephen D. Moore's suggestion that that the use of imperial themes and motifs in Revelation create a self-perpetuating cycle that lead to one imperial power being replaced by another. This article presents an alternative reading of the book of Revelation: first, acknowledging as significant the text's status as apocalyptic literature, written as a device of inspiration and subversion against reigning powers. Such literature is shown to deliberately employ imperial themes and motifs in order to subvert imperial rule; it serves as fantasy, exposing the 'hidden structures of false power' and suggesting an alternative. This leads to a reading of the text using Scott's theories of hidden transcripts. As a hidden transcript, the text serves as an anti-authoritarian device that reflects popular feelings toward an oppressor through symbolism and codes. It represents a community's secret longing for a day of victory over their oppressors; ultimately, the inversions and mimicry of the text serve to equalize and level class structures rather than reverse them. In order to facilitate a reading that truly represents this and allows the text to speak for itself, the article suggests an understanding of the book of Revelation as a dramatic work grounded in the performance art of the Roman Empire. It engages as an example Revelation 5 in the manner of a recitatio of the early empire, highlighting the discontinuity between what is seen and heard, before further exploring the ramifications of such a reading. Though in its early stages, such a reading of Revelation returns an ambiguity and depth to the text that certain postcolonial methods are lacking, whilst acknowledging its impact as a complex literary work that seeks not to provide answers, but rather a vision of hope that stands as an alternative to the forces of empire surrounding it.